Assessing chest radiographic quality and the influence of COVID‐19 pathology: the Australian experience - Peter O'Reilly; Dania Abu Awwad; Sarah Lewis; Ernest Ekpo; Warren Reed (Journal of Medical Radiation Sciences)
Abstract Introduction Quality assurance (QA) in medical imaging ensures consistently high‐quality images at acceptable radiation doses. However, the applicability of the chest X‐ray (CXR) QA tool in images with pathology, particularly infectious diseases like COVID‐19, has not been explored. This study examines the utility of the European Guidelines for image quality in QA of CXRs with varying severity and types of infectious disease. Methods A convenient sampling methodology was employed to recruit 25 participants (qualified radiographers: n = 13 and 4th‐year undergraduate radiography students: n = 12) to evaluate 70 CXR images using the European Guidelines for image quality in CXRs. The image dataset comprised of COVID‐19 and non‐COVID‐19 cases, which were randomly selected to reflect routine clinical practice variability. Participants independently rated image quality based on 10 criteria in the European guidelines on quality criteria for CXRs using a six‐point Likert scale. Image quality ratings of normal and pathological CXR images were compared using a Kruskal–Wallis test. Spearman's ranked order correlation was used to assess the association between quality criteria ratings. Results CXRs with no pathology or non‐COVID pathologies exhibited statistically higher total QA scores compared to CXRs with COVID‐19 and indeterminate COVID‐19 (P < 0.001). This trend was evident across various QA factors, especially those associated with patient inspiration. Higher levels of infection corresponded to lower QA ratings. No differences were found between different pathologies regarding the medial border of the scapulae being outside the lung fields. Conclusions Severe pathology negatively impacts the technical quality of CXRs with COVID‐19 features without necessarily affecting their diagnostic value. The findings emphasise the need to prioritise diagnostic ability over technical quality when evaluating CXRs exhibiting diffuse signs of pathology.